Hypnosis measured with monitors of anesthetic depth – EEG changes during the test for Harvard Group Scale of Hypnotic Susceptibility - Zech, Nina; Seemann, Milena; Hansen, Ernil (Frontiers in Psychology, 2023)
Introduction: Hypnotic trance can be defined as a non-ordinary state of consciousness that is accompanied by a number of neurophysiological changes including brain electrophysiology. Besides subjective measures corresponding objective parameters are needed in experimental and clinical hypnosis research, but are complex, impractical, or unspecific. A similar challenge exists for measurement and monitoring of non-drug induced hypnosis, namely general anaesthesia. There, observation of changes in EEG induced by narcotics has led the development of monitors for depth of anaesthesia based on EEG parameters. We investigated whether two such monitors react to induction and maintenance of hypnosis during a highly standardized procedure. Methods: 56 volunteers were monitored for Bispectral Index (BIS) and Cerebral State Index (CSI) (range 0-100, >95 considered “awake”) during test of Harvard Group Scale of Hypnotic Susceptibility. For this test, trance is induced by a taped text and followed by 12 tasks performed under hypnosis. In contrast to random forms of hypnosis, this represents a standardized, world-wide established condition. According to the resulting score participants were classified into suggestibility groups in order to evaluate whether the electrophysiological measurements of BIS and CIS indices differ between high and low suggestible persons. Furthermore, participants were asked to rate their hypnotic depth (HD, 1-10) at every task of the test. Results: Scores dropped significantly from a mean of 97.7 to 86.4 for BIS, and from 94.6 to 77.7 for CSI with induction of hypnosis, to stay throughout hypnosis at levels of about 88.6 or 82.9, respectively. Results did not differ between high and low suggestible participants. The means of the subjective score of hypnotic depth and of the electrophysiological measurements showed a similar course. However, no correlation was found between BIS or CSI values and scores of hypnotic depths. Conclusions: Monitors for depth of anaesthesia respond to changes of consciousness including trance state of hypnosis. However, specificity is unclear. Pragmatically, in hypnosis research with exclusion of drug effects or sleep these monitors might be helpful to test and compare efficacies of induction texts and to detect disturbances of trance state.